PENGEMBANGAN BUKU SAKU MATEMATIKA PADA MATERI OPERASI HITUNG PERKALIAN PECAHAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V DI SD SWASTA TRI BAKTI - Aziz Sukma; Nuri Ramadhan (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2023)
This research aims to develop and test the effectiveness of a mathematics pocketbook on the topic of fraction multiplication in improving the learning outcomes of fifth-grade students at Tri Bakti Private Elementary School. The research approach used is the development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis stage includes the analysis of students' and teachers' needs as well as curriculum analysis. In the design stage, the pocketbook is designed according to the results of the analysis. The development stage involves expert validation and product revision based on feedback from validators. Implementation is carried out with a limited trial on 24 fifth-grade students to measure the effectiveness of the pocketbook. Evaluation is conducted through data analysis from the trial results, including pre-tests and post-tests, as well as student response questionnaires. The results show that the developed pocketbook is effective in improving students' learning outcomes. Students who used the pocketbook showed significant improvement in their learning outcomes compared to before using the pocketbook. Additionally, student responses to the pocketbook were very positive, indicating that this learning media is engaging and motivating for them in learning mathematics. The pocketbook contributes positively to the learning process by presenting the material in a concise, clear, and interesting manner. In conclusion, this mathematics pocketbook on the topic of fraction multiplication can be used as an alternative effective learning medium to improve the learning outcomes of fifth-grade students at Tri Bakti Private Elementary School.